2019
DOI: 10.7755/fb.117.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Using oxytetracycline validation for confirmation of changes in vertebral band-pair deposition rates with ontogeny in sandbar sharks (Carcharhinus plumbeus) in the western North Atlantic Ocean

Abstract: Age underestimation of many shark species, such as the sandbar shark (Carcharhinus plumbeus), has been proven with age validation methods including bomb radiocarbon dating, oxytetracycline (OTC) injection, and tagrecapture data. Validation studies indicate that band-pair deposition in vertebral centra may not be directly related to time, especially in older individuals of a species. In this study, vertebrae from tagged, OTCinjected, and recaptured sandbar sharks were examined to determine if band-pair depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(40 citation statements)
references
References 12 publications
(39 reference statements)
5
34
1
Order By: Relevance
“…Significant differences in growth characteristics of bonnetheads have been found between populations in the GOM and the Atlantic region (Frazier et al, 2014). For the population in the Atlantic region, estimated maximum age (males: 12.0 years; females: 17.9 years) and age at 50% maturity (males: 3.9 years; females: 6.7 years) are more than twice the estimates for the population in the GOM (males: 5.5+ years for maximum age, 1.7 years for age at 50% maturity; females: 7.5+ years for maximum age, 2.9 years for age at 50% maturity) (Lombardi-Carlson et al, 2003;Frazier et al, 2014). Previous age and growth studies of bonnetheads in the eastern GOM (Parsons, 1993;Carlson and Parsons, 1997;Lombardi-Carlson et al, 2003) found significant latitudinal variation in life history traits; however, latitudinal variation has not been detected in the population off the Atlantic coast (Frazier et al, 2014).…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…Significant differences in growth characteristics of bonnetheads have been found between populations in the GOM and the Atlantic region (Frazier et al, 2014). For the population in the Atlantic region, estimated maximum age (males: 12.0 years; females: 17.9 years) and age at 50% maturity (males: 3.9 years; females: 6.7 years) are more than twice the estimates for the population in the GOM (males: 5.5+ years for maximum age, 1.7 years for age at 50% maturity; females: 7.5+ years for maximum age, 2.9 years for age at 50% maturity) (Lombardi-Carlson et al, 2003;Frazier et al, 2014). Previous age and growth studies of bonnetheads in the eastern GOM (Parsons, 1993;Carlson and Parsons, 1997;Lombardi-Carlson et al, 2003) found significant latitudinal variation in life history traits; however, latitudinal variation has not been detected in the population off the Atlantic coast (Frazier et al, 2014).…”
mentioning
confidence: 87%
“…For the population in the Atlantic region, estimated maximum age (males: 12.0 years; females: 17.9 years) and age at 50% maturity (males: 3.9 years; females: 6.7 years) are more than twice the estimates for the population in the GOM (males: 5.5+ years for maximum age, 1.7 years for age at 50% maturity; females: 7.5+ years for maximum age, 2.9 years for age at 50% maturity) (Lombardi-Carlson et al, 2003;Frazier et al, 2014). Previous age and growth studies of bonnetheads in the eastern GOM (Parsons, 1993;Carlson and Parsons, 1997;Lombardi-Carlson et al, 2003) found significant latitudinal variation in life history traits; however, latitudinal variation has not been detected in the population off the Atlantic coast (Frazier et al, 2014). High degrees of site fidelity have been documented for this species (Heupel et al, 2006;Driggers et al, 2014), and tagging data indicate that there is no mixing between populations in the GOM and Atlantic region (Kohler and Turner, 2019).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…[63][64][65][66][67][68][69][70][71]. However, this is questioned by recent studies [72][73][74] and especially in old individuals of long living species the age determination seems to be highly underestimated as the growth rate decreases with age resulting in a band width decline at the centrum edges that can become unresolvable in older individuals [56,72,[75][76][77][78][79]. The section of EMRG-Chond-SK-1b revealed 31 band pairs (birth mark + 30 band pairs), suggesting, under the assumption of an annual growth band deposition, that EMRG-Chond-SK-1 was around 30 years old.…”
Section: Plos Onementioning
confidence: 99%